Data Science Applied to Carbon Materials: Synthesis, Characterization, and Applications (Adv. Theory Simul. 2/2022). Issue 2 (10th February 2022) - Morelos‐Gomez, Aaron; Terrones, Mauricio; Endo, Morinobu
Abstract : Data Science Applied to Carbon Materials Carbon materials have been the main subject for two Nobel prizes; they exhibit excellent physical and chemical properties that have been used in diverse applications. In article number 2100205, Morelos‐Gomez, Terrones and Endo explore how, with the aid of tools from data science, carbon nanomaterials research and development can accelerate in three key experimental areas: synthesis, characterization, and applications.